RADICULAR GROOVE OF MAXILLARY PREMOLAR: IS A "DANGER ZONE"? - Ahmet Mert Nalbantoğlu; Deniz Yanık (Cumhuriyet University, 2022)
Objectives: To evaluate the presence of radicular groove and dentin thickness on the palatal aspect of the buccal root of maxillary first premolars using cone-beam computed tomography (CBCT). Materials and methods: Images of 312 maxillary first premolars belonging to 187 patients (between 18-69 years, 94 females and 93 males) who were referred to the clinic were retrospectively reviewed. Root canal treatment, periapical lesion, and post-core were excluded. One and three-rooted premolars were also excluded. CBCT images were viewed on the axial plane to detect grooves. The concave area on the palatal aspect of the buccal root was recorded as a groove. Buccal and palatal dentin thicknesses were measured by two observers at the level of 3 mm below furcation. Statistical analyses were performed. Results: Buccal and palatal thicknesses were 1.28(±0.25) and 0.87(±0.13) mm, respectively. According to Student's t-test, buccal dentin thickness was statistically higher than palatal dentin (p=0.016). The prevalence of groove was 82.05%. While palatal thickness without groove was 0.93(±0.14) mm, palatal thickness corresponding to groove was 0.82(±0.12) mm. One-way ANOVA showed palatal and buccal thickness in group 1 (18-35 years) was statistically lower than group 3 (>65 years) (p=0.012 and p=0.003). No statistical difference in thickness was observed between sex and left or right side (p>0.05). Conclusions: Palatal thickness related to groove can be considered a "danger zone" for post-core and endodontic treatment. Considering the high prevalence (82.05%) and thin dentin of the groove, more conservative canal and post space preparation and CBCT examination are recommended to avoid perforation.